A Dual Role Reductase from Phytosterols Catabolism Enables the Efficient Production of Valuable Steroid Precursors. Issue 10 (19th January 2021) - Peng, Haidong; Wang, Yaya; Jiang, Kai; Chen, Xinru; Zhang, Wenlu; Zhang, Yanan; Deng, Zixin; Qu, Xudong
Abstract: 4‐Androstenedione (4‐AD) and progesterone (PG) are two of the most important precursors for synthesis of steroid drugs, however their current manufacturing processes suffer from low efficiency and severe environmental issues. In this study, we decipher a dual‐role reductase (mnOpccR) in the phytosterols catabolism, which engages in two different metabolic branches to produce the key intermediate 20‐hydroxymethyl pregn‐4‐ene‐3‐one (4‐HBC) through a 4‐e reduction of 3‐oxo‐4‐pregnene‐20‐carboxyl‐CoA (3‐OPC‐CoA) and 2‐e reduction of 3‐oxo‐4‐pregnene‐20‐carboxyl aldehyde (3‐OPA), respectively. Inactivation or overexpression of mnOpccR in the Mycobacterium neoaurum can achieve exclusive production of either 4‐AD or 4‐HBC from phytosterols. By utilizing a two‐step synthesis, 4‐HBC can be efficiently converted into PG in a scalable manner (100 gram scale). This study deciphers a pivotal biosynthetic mechanism of phytosterol catabolism and provides very efficient production routes of 4‐AD and PG. Abstract : An unusual reductase (mnOpccR) in phytosterol catabolism is found to catalyze the formation of 4‐HBC through two different routes. Inactivation or overexpression of mnOpccR leads to exclusive production of 4‐androstenedione (4‐AD) and 4‐HBC from phytosterols. By a two‐step synthesis, 4‐HBC can be further efficiently converted into progesterone (PG). This work provides two green and economical methods for 4‐AD and PG manufacturing.